How unique is the low oxygen response? An analysis of the anaerobic response during germination and comparison with abiotic stress in rice and Arabidopsis - Narsai, Reena; Whelan, Jim (Frontiers in Plant Science, 2013)
Plants face a variety of environmental stresses and have evolved molecular mechanisms to survive these challenges. One of these stresses is low-oxygen conditions, which can occur under flooding stress. Rice (Oryza sativa) is somewhat unique for its ability to tolerate and even germinate under low to no oxygen conditions. In this study we examined global transcriptomic responses over the course of germination and in response to low-oxygen and abiotic stresses in rice and Arabidopsis (Arabidopsis thaliana).Over 150 microarray datasets were analysed in parallel to determine just how unique the low oxygen response is in rice. Comparison of germination under aerobic conditions in rice and Arabidopsis, with anaerobic germination in rice revealed conserved transcriptomic responses that are not only conserved across both species but also occur in the absence of oxygen in rice. Thus, these genes may represent functions necessary for the developmental progression of germination, whether or not oxygen is present in rice.Analysis of genes that responded differently in rice compared to Arabidopsis revealed responses specific to anaerobic germination in rice, including the down-regulation of genes encoding redox functions and up-regulation of receptor kinases. Comparison of a range of hypoxia/anoxia studies within and across Arabidopsis and rice revealed conserved and species specific changes in gene expression (e.g. Arabidopsis specific up-regulation of WRKYs and rice specific down-regulation of heme), unveiling unique transcriptomic signatures of the low-oxygen response. Lastly, a comparison of the low-oxygen response with cold, salt, drought and heat stress revealed some similarity with the response to heat stress in Arabidopsis, which was not seen in rice. Comparison of these heat-responsive, abiotic stress marker genes in Arabidopsis with their rice orthologues revealed that while low-oxygen may be perceived as an abiotic stress in Arabidopsis, this is not the case in rice.